Community Empowerment Through Assistance in Making Business Identification Numbers as the Legality of Micro, Small and Medium Enterprises in Kedung Baruk Village, Rungkut District - Elfrida Laras Candrakusuma Ardine; Fatma Nur Arofah; Binti Azizatun Nafi'ah (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Kedung Baruk Village has various types of businesses occupied by local residents such as convection, grocery stores, culinary, and so on. As business develops, MSMEs in Kedung Baruk need a Business Identification Number (NIB) to fulfill the urgency of business legality. There are still many Kedung Baruk Village residents who do not understand NIB and its benefits. The purpose of this community service is to help Kedung Baruk residents get their business legalized by assisting MSME players to make NIB and explaining the benefits of having the NIB. The method in the assistance program for making NIB is to record MSMEs that do not yet have NIB, conduct socialization and assistance in making NIB for MSMEs, and submit physical NIB documents to MSME actors. There were positive results in this service activity, namely with this NIB socialization activity, MSMEs were educated about the urgency of the importance of legality in running a business. From the data obtained regarding the number of MSMEs in the Kedung Baruk Village, previously only 21 MSMEs had NIB, then an additional 15 MSMEs became 36 MSMEs.